OPTIMALISASI SUMBER DAYA DATA UNTUK INOVASI LAYANAN BANK SYARIAH DI ERA DIGITAL - Fadillah Syafitri; Risa Adelila Hasibuan; Salma Indriani; Nurbaiti Nurbaiti (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This study aims to examine how the optimization of data resources drives service innovation in Islamic banking in the digital era. Digital transformation through Big Data Analytics, artificial intelligence, digital banking platforms, and technologies such as APIs and cloud computing has positioned data as a strategic asset for Islamic banks. Effective utilization of data enhances operational efficiency, supports personalized services, strengthens risk management, and enables the development of Sharia-compliant financial products. This research employs a qualitative library-based approach by analyzing fifteen scholarly articles related to digitalization, service innovation, green banking, and data management in Islamic finance. The findings indicate that data optimization significantly contributes to accelerating digital service adoption, improving customer satisfaction, expanding Islamic financial inclusion, and reinforcing governance based on the principles of maqashid shariah. However, digitalization also presents challenges, including cybersecurity threats, limited technological infrastructure, low digital literacy in Sharia-compliant finance, and insufficient human resource competencies. Therefore, integrated strategies involving strengthened Sharia governance, enhanced technological capabilities, and collaboration with regulators and FinTech institutions are required to build a secure, inclusive, and sustainable digital Islamic financial ecosystem.